Synthesis of α,α-Disubstituted Benzocyclobutane Amino Acids through [2+2] Annulation of Benzyne with Dehydroalanine - Picard, Audrey; Ciblat, Stephane; Ramtohul, Yeeman K. (Synlett, 2020)
A mild and general method for the synthesis of α,α-disubstituted benzocyclobutane amino acids through a [2+2] annulation of benzyne with dehydroalanine is described. Yields up to 88% of the constrained quaternary amino acids can be obtained and its application in peptidomimetic synthesis is demonstrated.
Keywords: benzyne; aryne; dehydroalanine; α,α-disubstituted benzocyclobutane amino acids; peptidomimetic